Isolation of high quality RNA from soil-grown Ilex paraguariensis roots suitable for next-generation sequencing and gene expression analyses - Avico, Edgardo Hernán (2017)
Fil: Avico, Edgardo Hernán. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.